Between ontology and representation: Locating Gilles Deleuze's 'difference-in-itself ' in and for geographical thought. (October 2017) - Cockayne, Daniel G.; Ruez, Derek; Secor, Anna
The concept of difference has long been integral to geographical thought. However, it is rare for geographers to consider precisely what difference is, or how it functions, and there are several contrasting traditions through which difference is understood. We argue that geographers could helpfully extend their theorizations of difference through Deleuze's philosophy of 'difference-in-itself'. We examine the value of a 'difference-in-itself' that views difference as generative, originary, and primary, in productive tension with conceptions of difference that tend to, purposefully or otherwise, subordinate difference to presupposed identity-based, representational categories, or dialectical forms of contradiction and opposition.